A Novel Method Ensuring an Immediate Target Angle After Horizontal Strabismus Surgery in Children - Fu, Joa-Jing; Hsieh, Meng-Wei; Lee, Lung-Chi; Chen, Po-Liang; Wen, Liang-Yen; Chen, Yi-Hao; Chien, Ke-Hung (Frontiers in Medicine, 2022)
Purpose: Pediatric strabismus surgery has low success rates and high reoperation rates because of difficult alignment measurements and the nature of different strabismus types. Furthermore, adjustable sutures are not easily employed in children on an OPD basis. Methods: This was a retrospective comparative case study of children less than 12 years old who underwent strabismus surgery and were followed up at least 6 months postoperatively. We proposed a novel method that combines adjustable sutures and corneal light reflexes in regular strabismus surgery to improve surgical results. Efficacy and safety were evaluated and compared with those in a regular fixed-suture group. Results: In total, 128 children (88: exotropia and 41: esotropia) in the novel method group (Group 1) and 109 (71: exotropia and 38: esotropia) in the regular fixed-suture group (Group 2) were enrolled. The primary outcome was the immediate target angle (for esotropia within 4 PD of orthotropia and exotropia within 8 PD of esotropia within the first week postoperatively); the secondary outcome was success at the 6-month visit (angle of deviation < 10 PD). Consequently, there was a significantly higher proportion of achieving the immediate target range and success rate in both exotropic and esotropic patients in Group 1 than in Group 2. A significantly lower reoperation rate was also demonstrated in Group 1. No complications were noted in either group. Conclusions: The novel method enabled a higher proportion of subjects to achieve an immediate target range and success rate and a lower chance of reoperation among both esotropic and exotropic patients.